In-Situ DRIFT Study of Au-Ir/Ceria Catalysts: Activity and Stability for CO Oxidation - Aguirre, Alejo (2016)
Monometallic gold and iridium, and bimetallic gold-iridium on ceria catalysts were synthesized by deposition-precipitation with urea. The activity of these ceria supported catalysts for CO oxidation was: Au-Ir >> Au > Ir. The bimetallic catalyst was highly active and stable during the carbon monoxide oxidation reaction, showing synergism between both metals. The catalysts were thoroughly characterized chemical and structurally. High-resolution electron microscopy coupled with energy dispersive spectroscopy and X-ray photoelectron spectroscopy showed evidences of iridium-gold intimacy. In situ infrared spectroscopy in the diffuse reflectance (DRIFT) mode was used to investigate the reactivity of the active sites. Concentration-modulation excitation spectroscopy (c-MES) allowed selective identification of intermediates and spectator species. CO chemisorbed onto iridium sites (2096, 2060 and 2012 cm-1) was found inactive, whereas carbon monoxide on metallic gold sites (Au0-CO, 2110 cm-1) exhibited reactivity for CO oxidation. In the bimetallic catalyst, new active sites (Au(-)-CO, 2095 and 2026 cm-1) together with Au0-CO species were observed, most likely produced by the isolation and stabilization of gold atoms by iridium.